Cardy expansion of 3d superconformal indices and corrections to the dual black hole entropy - Alfredo González Lezcano; Maximilian Jerdee; Leopoldo A. Pando Zayas (Journal of High Energy Physics, 2023)
Abstract We consider the superconformal index of three-dimensional N $$ \mathcal{N} $$ = 2 supersymmetric field theories computed via localization on S 1 × S 2. We systematically develop an expansion where the ratio of the radius of S 1 to the radius of S 2 is taken very small — a Cardy-like expansion. We emphasize the sub-leading structures in this Cardy-like expansion as well as their interplay with the large-N limit for theories with gauge group of the form product of U(N) factors. We demonstrate that taking the large-N limit first leads to an expression for the effective action yielding the index that only includes terms proportional to 1/β and powers of β i=0,1,2 where β is the ratio of radii. As we depart from the β → 0 limit for finite N, we find indications of non-perturbative contributions of the form e −1/β . We present an explicit evaluation of the superconformal index for the ABJM theory in the large-N limit that is exact in β up to non-perturbative corrections. For the ABJM theory we explore the implications of the Cardy-like expansion for corrections to the entropy of the rotating, electricallly charged, asymptotically AdS4 dual black hole. Interestingly, we find a closed form for the entropy that includes all perturbative corrections in β and takes the form of the leading order expression but with shifted charges.